Factors associated with and consequences of open conversion after laparoscopic distal pancreatectomy: initial experience at a single institution. Issue 12 (21st July 2016) - Goh, Brian K. P.; Chan, Chung Yip; Lee, Ser Yee; Chan, Weng Hoong; Cheow, Peng Chung; Chow, Pierce K. H.; Ooi, London L. P. J.; Chung, Alexander Y. F.
Abstract : Background: Laparoscopic distal pancreatectomy (LDP) is increasingly adopted today. This study aims to determine factors associated with and consequences of open conversion after LDP. Methods: Retrospective review of the first 40 consecutive LDP performed for pancreatic tumors from 2006 to 2015 was performed. Individual surgeon volume was stratified by ≤5 versus >5 cases and institution experience was stratified by two time periods 2006–2010 and 2011–2015. Results: Two high‐volume surgeons performed 19 cases with an average case volume of ≥2/year whereas 10 low‐volume surgeons performed 21 cases with an average case volume of <1/year. Median age of patients was 57.6 (range, 21–78) years. LDP was performed for malignancy in four (10%) patients. The median tumor size was 25 (range, 8–75) mm. Eight patients (20%) underwent subtotal pancreatectomies and seven (17.5%) had concomitant surgeries. Eleven (27.5%) LDP were spleen‐saving procedures. Ten (25%) procedures were converted to open. Twenty‐nine (72.5%) patients experienced 90‐day/in‐hospital morbidity of which eight (20%) were major (>grade II). There were 24 (60%) pancreatic fistulas of which 10 (25%) were grade B. Univariate analyses demonstrated that splenectomy (10 (34.5%) versus 0, P  = 0.025), individual surgeon volume (<5 cases) (8 (38.1%) versus 2 (10.15%), P  = 0.044) and institution experience (5 (55.6%) versus 5 (16.1%), P  = 0.016) were factors associated with open conversion after LDP. Open conversion was associated with an increased rate of intra‐operative blood transfusion ( P  = 0.053). Conclusions: Splenectomy, institution experience and individual surgeon volume were the factors associated with open conversion after LDP.